A 'cold heart' papule. (1st October 2021) - Infusino, S. D.; Magnano, M.; Ioris, T.; Rech, G.; Girardelli, C. R.; Barbareschi, M.; Vianello, L.; Balestri, R.
Abstract: Click here for the corresponding questions to this CME article.